DIASTOLIC DYSFUNCTION AND REMODELING LEFT VENTRICLE DEPENDING ON THE CONTROL GLYCEMIA IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - Normatov Murod Buribayevich (Journals Park Publishing, 2022)
It is proved that type 2 diabetes mellitus (DM), the incidence of which has been continuously increasing in recent years, is an independent risk factor for the development of coronary heart disease (CHD). The presence of DM in patients with coronary heart disease significantly increases the likelihood of developing chronic heart failure (CHF), and is also a predictor of death in patients with CHF. At the same time, it was shown that 30-50% of DM patients with a transient decrease in local myocardial contractility do not have hemodynamically significant lesions of the coronary arteries, which indicates the presence of a specific myocardial condition – diabetic cardiomyopathy. Its existence was confirmed by the Framingham study, in which revealed a large thickness and mass of the myocardium of the left ventricle (LV) in patients with DM. It is believed that an increase in the diastolic stiffness of the myocardium is one of the characteristic features of diabetic cardiomyopathy, since disorders of LV diastolic function are its earliest manifestations. To date, numerous studies have proven the effectiveness of strict glycemic control in reducing the risk of development and progression of various complications of diabetes.
Keywords: type 2 diabetes mellitus, diabetic cardiopathy, arterial hypertension